Compression Behavior of CFST Stub Columns with Holes - Yanhua Liu; Qingxin Ren; Yuqing Li (Advances in Civil Engineering)
Holes are always opened in the steel tubes during the inspection and revision of initial concrete imperfections in concrete filled steel tubular (CFST) columns. The structural performance of such composite columns with holes may have obvious differences in comparison with normal CFST members. This paper intends to investigate the influences of sectional type, holes location, holes size, and holes depth on CFST stub columns. The typical failure modes, load-deformation responses, the ultimate strength, and ductility were discussed in detail. A total of twenty-eight specimens, twenty CFST  columns with holes, four intact CFST  specimens, and four reference hollow steel tubes subjected to axial compressive loading, were tested. The experimental results were compared with predictions of Eurocode 4 and finite element analysis. An empirical equation for predicting the ultimate strength of CFST stub columns with holes was proposed.